Purslane (Portulaca Oleracea): A Prospective plant Source of Nutrition and its waste utilization in traditional product - Ayesha Jamal; Navita Pareek (Research Synergy Foundation, 2022)
The purpose of this review is to study powder leaves of purslane (Portulaca oleracea). It is one of India's most widely cultivated and popular vegetables. Purslane (P. oleracea) leaves are rich in beta-carotene, iron, and calcium source. This leaves categories as waste products, however, can be used for the treatment of anemia and people with micronutrient inadequacies in value-added products. This analysis evaluated the nutritional profile of powder and its use in purslane leaves. For drying leaves at different temperatures for a particular period there are a variety of drying methods, such as dryers for hot oven and sun drying methods. It can be stored in the lean season after drying. They are also rich in beneficial plant metabolities, including sulfur that contains glucosinolates, anthocyanin, flavonoids, and other compounds for improving nutrient, physical-chemical, sensorial, and health benefits. Purslane leaves phytochemicals are more powerful antioxidants that can reduce the risk of chronic diseases by protecting against free radicals.